(untitled) (Global Journal of Human-Social Science, 2022)
The purpose of this paper is to provide some theoretical and empirical elements to measure the level of governance using an empirical case that will focus on the analysis of the 2015-2021 administration of the Government of the State of Nuevo Le n The governance model is evaluated based on the weighting of the degree of effectiveness efficiency and legitimacy that can be observed from the analysis of state public management and the evaluation of some public policies For the development of the project the World Bank s governance index is used as a reference which includes the measurement of six variables